The Honesty of Taxpayer as Factor of the State Security: Realities of Tax Legislation and Judicial Practice of Ukraine - Igor Ivanovich Babin (Societas et Iurisprudentia, 2017)
In this study, the category of the “honesty of taxpayer” and features of its application in the tax legislation and judicial practice of Ukraine are analysed. Explained are also the evaluation and subjective character of this category, because the clear criteria of the honesty in law are absent and judicial practice is characterised by an extraordinarily wide set of such criteria and by different application of them. Tax organs and courts in their struggle with abuse of rights by taxpayers avoiding payments of taxes use the category “honesty of taxpayer”. However, if dishonesty is one of manifestations of abuse of the civil or tax rights by taxpayers, it is simple to discover that the current tax legislation has facilities to influence such taxpayers. The category “honesty” has rather moral and ethical than juridical nature and comes out from the maintenance of the Constitutional norms which provide for the social and democratic character of Ukraine. At the same time, the mechanical use of this unjuridical category in judicial practice by the decision-making in concrete tax disputes can result in violation of democratic and legal principles. Moreover, application of such category as “honesty” in the administrative legal proceedings can lead to illegal and groundless court decisions. Application of legal fiction “dishonesty taxpayer” for filling of blanks in tax legislation as well as application of tax penalties to taxpayers are: 1) violating the presumption of innocent taxpayer; 2) encouraging the judicial dishonesty of the tax organs; 3) conducing to judicial errors; 4) violating the balance of public and private interests in the legal state.